PEMBELAJARAN SEJARAH THINKING LIKE A HISTORIAN: CRITICAL READING, MIND-MAP, DAN CREATIVE WRITING - Mahrus Afandi (Universitas Negeri Malang, 2023)
LEARNING HISTORY THINKING LIKE A HISTORIAN: CRITICAL READING, MIND-MAP, AND CREATIVE WRITINGThe study of history should not rely on only one source or one authoritative narrative. The nature of history which necessitates a postulate that once a historical event is written, it immediately becomes something subjective. It is certain that a written historical event is absolutely influenced by the subjectivity of the author. Therefore, history learning does not require a single narrative. History learning must provide opportunities for students to practice historical thinking skills that contain sensitivity to the multiple causes of events, empathy toward an event investigated, and sensitivity to change and continuity. This article attempts to offer a history learning model that facilitates students to master historical thinking skills by using activities such as critical reading, mind-map making, and creative writing.Pembelajaran sejarah tidak seharusnya hanya mengandalkan satu sumber atau satu narasi yang dianggap otoritatif. Sifat dasar sejarah yang meniscayakan adanya ketetapan bahwa ketika suatu peristiwa sejarah ditulis, maka seketika itu pula menjadi sesuatu yang subjektif, karena dipastikan penulisan peristiwa sejarah tersebut sedikit-banyak dipengaruhi oleh subjektivitas penulisnya, itu tidak menghendaki adanya narasi tunggal. Oleh karena itu, pembelajaran sejarah harus disertai dengan upaya untuk menghadirkan kesempatan bagi peserta didik untuk melatih kemampuan berpikir kesejarahan yang mengandung sensitivitas terhadap multi penyebab dari suatu peristiwa, empati terhadap konteks peristiwa yang sedang dikaji, sensitivitas terhadap perubahan, dan keberlanjutan. Artikel ini mencoba untuk menawarkan model pembelajaran sejarah yang memfasilitasi peserta didik untuk menguasai kemampuan berpikir kesejarahan dengan memakai kegiatan seperti critical reading, pembuatan mind-map, dan creative writing.